QUALITATIVE RISK COVERAGE IN AGRICULTURE THROUGH DERIVATIVE FINANCIAL INSTRUMENTS BASED ON SELYANINOV INDICES - Cristian KEVORCHIAN; Camelia GAVRILESCU; Gheorghe HURDUZEU (Financial Studies, 2013)
The financial product designed by the authors belongs to the class of derivative financial instruments, having “weather conditions” as basic variable; the settlement is oriented to options on OTC markets, which are able to adapt to the farmers’ risk exposure level. Unfortunately, they cause certain problems at position liquidation, and, moreover, due to lack of stock prices, they require proper evaluation models. The transformation of the weather risk into financial risk and its trading on financial markets relies on the willingness for risk taking of those groups of farmers which are using this particular financial instrument. One needs to emphasize that the proposed product is covering the risk for the production segment only of a specific crop that cannot be covered by the regular agricultural insurance, and it is based upon the Selyaninov index. The calculation formulae for a put type option will be presented: pay-off, strike, tick,and the level of the insurance premium for cereals. The reference weather stations will be: Tulcea, Brăila, Buzău, Galaţi, Focşani and Medgidia.